TESTE DE ANTIBIOSE EXERCIDA PELO EXTRATO DOS LÃQUENS Parmelia tinctorum DESP. E Cora pavonia (WEB) E. FRIES - Mitidieri, J.; Joly, S.; Ferraz, E. C. (REVISTA DE AGRICULTURA, 2016)
TESTE DE ANTIBIOSE EXERCIDA PELO EXTRATO DOS LÃQUENS Parmelia tinctorum DESP. E Cora pavonia (WEB) E. FRIES